Mechanical characterization of sawn timber for structural use, graded visually in accordance with Spanish standard UNE 56544 - Fernández-Golfín, J. I.; Díez Barra, M. R.; Gutiérrez Oliva, A. (Materiales de Construcción, 1998)
The employment of timber in structures in Spain was hurting of the nonexistence of accepted calculation procedures. The recent adoption and publication of the Eurocode 5 compels to the employment of the characteristic values of the material in the structural calculation by the method of the finite elements. This report sets forth the results of the experiments carried out at INIA’s Forest Research Centre (CIFOR-INIA) regarding the mechanical characterization of sawn timber of size 150x50x3.000 mm and the structural uses of "Pinus sylvestris, P. radiata and P. pinaster" from different Spanish provenances. The characteristic values and strength classes corresponding with the grades stated in the Spanish standard UNE 56544 are also provided. The report compares and analyses the results of these experiments, and presents the conclusions drawn from the different behaviour shown by the four species. An analysis of the Spanish standard for the visual grading of structural timber is carried out on the three species.